Advanced multispectral image-processing endoscopy system for visualizing two-dimensional hemoglobin saturation and relative hemoglobin concentration - Chiba, Toru; Obara, Yoshimi; Murata, Masaharu; Akahoshi, Tomohiko (Endoscopy International Open, 2019)
Background and study aims The association of tumor hypoxia and vascularization with malignant progression is recognized, and detection by measuring tissue hemoglobin (Hb) saturation and concentration has attracted attention. In this study, we designed a simple algorithm and multispectral image-processing endoscopy system to map relative Hb concentration and Hb saturation for detection of tumors in small animal viscera in vivo.Materials and methods We designed and validated an optical filter-equipped endoscope system for two-dimensional visualization of Hb concentration and saturation maps and used it in a real-time video examination. A simplified method based on spectral data capture and analysis of defuse reflection of mucosa, including image capture and data processing of the spectral features of Hb oxygenation, was developed.Results An Hb saturation calibration curve was obtained. Then, differences in oxygenation levels between normal mucosa and in vivo tumors in a small animal model were determined by using the new method and endoscope system.Conclusions A multispectral image-processing endoscopic system with a mapping frame rate comparable to that of white light imaging systems (7.5 frames/second) was developed.